In vitro oxidations of low-density lipoprotein and RAW 264.7 cells with lipophilic O(3P)-precursors. Issue 44 (15th July 2020) - Petroff, John T.; Isor, Ankita; Chintala, Satyanarayana M.; Albert, Carolyn J.; Franke, Jacob D.; Weinstein, David; Omlid, Sara M.; Arnatt, Christopher K.; Ford, David A.; McCulla, Ryan D.
Abstract : Lipophilic O( 3 P)-precursors generate 2-hexadecenal upon UV-irradiation. Abstract : A beneficial property of photogenerated reactive oxygen species (ROS) is the capability of oxidant generation within a specific location or organelle inside a cell. Dibenzothiophene S -oxide (DBTO ), which is known to undergo a photodeoxygenation reaction to generate ground state atomic oxygen [O( 3 P)] upon irradiation, was functionalized to afford localization within the plasma membrane of cells. The photochemistry, as it relates to oxidant generation, was studied and demonstrated that the functionalized DBTO derivatives generated O( 3 P). Irradiation of these lipophilic O( 3 P)-precursors in the presence of LDL and within RAW 264.7 cells afforded several oxidized lipid products (oxLP) in the form of aldehydes. The generation of a 2-hexadecenal (2-HDEA ) was markedly increased in irradiations where O( 3 P) was putatively produced. The substantial generation of 2-HDEA is not known to accompany the production of other ROS. These cellular irradiation experiments demonstrate the potential of inducing oxidation with O( 3 P) in cells.